Settlement pottery from the Early Iron Age in Kras - Vinazza, Manca (Arheološki vestnik, 2021)
The article discusses pottery material from three Early Iron Age hillforts, where excavations have been carried out in the last 30 years. These present a starting point for the establishment of a chronological picture of settlement pot- tery in Kras region. In addition to stratigraphic data, macroscopic analysis of the pottery technology and comparative study of the finds with other contemporary sites in the area of Caput Adriae have been performed. The established chronological picture of the settlement pottery presents the first attempt of this kind to create a pottery overview for the discussed territory.